Abstract ID: 124 Application expansion of the Monte-Carlo based treatment planning system for BNCT to particle radiotherapy and X-ray therapy. (October 2017) - Kumada, Hiroaki; Takada, Kenta; Aihara, Teruhito; Matsumura, Akira; Sakurai, Hideyuki; Sakae, Takeji
Abstract : University of Tsukuba is developing an accelerator-based treatment device for boron neutron capture therapy (BNCT). As part of the development, a Monte-Carlo based treatment planning system (developing code: Tsukuba-Plan) is being developed[1] . The Tsukuba-plan has employed PHITS as the Monte-Carlo transport calculation code[2] . PHITS can calculate neutron, photon as well as proton and heavy-ions including carbon-ions. Therefore, Tsukuba-Plan with PHITS enables to perform dose estimations for not only BNCT but also particle radiotherapy and X-ray therapy. In BNCT protocols for malignant brain tumor, X-ray therapy is added after BNCT to enhance the treatment effect. And in the future, proton therapy will be also applied in stead of the X-ray therapy in order to improve therapeutic dose distribution. Therefore, the treatment planning system is required dose estimation for the combined multi-modality therapy. Based on this background, the aim of this study is to expand application field of the Tsukuba-plan to conventional external radiotherapies. University of Tsukuba Hospital has X-ray therapy, proton therapy and BNCT. Thus, first, we have expanded Tsukuba-plan to proton therapy and X-ray therapy. Regarding proton therapy, we have constructed 155 MeV and 200 MeV proton beam source and a geometry struction data for the proton therapy device installed in our Hospital. Verification for calculation accuracy for proton irradiation were performed. Phantom experiments performed using the proton therapy device in advance were represented by the Tsukuba-Plan. The proton dose distributions in the phantom were determined, and the calculations were compared with the experimental values. Calculations for both of proton therapy and X-ray therapy were in good agreement with experimental values, respectively. The results demonstrated that the Tsukuba-Plan enables to estimate accurately doses for proton irradiation and X-ray irradiations. To put Tsukuba-Plan to practical use for proton therapy and X-ray therapy, Tsukuba-Plan is improved further and several verifications are performed. This work was supported by JSPS KAKENHI Grant Nos. JP16K15343.